Effect of Soybean Straw and Seaweed (Sargassum johnstonii) Based Total Mixed Ration on Feed Intake, Digestibility and Rumen Fermentation in Crossbred Cows - Pandya, P R; Katwal, Sarishti; Sorathiya, K K; Patel, Y.G.; Shah, S.V.; Parmar, D.J. (Indian Journal of Animal Nutrition, 2022)
An experiment was conducted to evaluate the effect of soybean straw and seaweed supplementation on feed intake, nutrient digestibility and rumen fermentation in lactating crossbred cows. Six Holstein Friesian X Kankrej (50:50) crossbred cows were used in Switch over design for 135 days with three periods each of 45 days duration. The animals received three treatments as total mixed ration viz., T1: TMR with compound concentrate mixture (60%) and wheat straw (40%); T2: TMR with compound concentrate mixture (60%), wheat straw (20%) and soybean straw (20%); T3: TMR with 8% seaweed (Sargassum johnstonii). The DM and DCP intake were at par in T1 and T2 but significantly (P